Expanded allogeneic adipose-derived mesenchymal stem cells (Cx601) for complex perianal fistulas in Crohn's disease: a phase 3 randomised, double-blind controlled trial. Issue 10051 (24th September 2016) - Panés, Julián; García-Olmo, Damián; Van Assche, Gert; Colombel, Jean Frederic; Reinisch, Walter; Baumgart, Daniel C; Dignass, Axel; Nachury, Maria; Ferrante, Marc; Kazemi-Shirazi, Lili; Grimaud, Jean C; de la Portilla, Fernando; et al.
Summary: Background: Complex perianal fistulas in Crohn's disease are challenging to treat. Allogeneic, expanded, adipose-derived stem cells (Cx601) are a promising new therapeutic approach. We aimed to assess the safety and efficacy of Cx601 for treatment-refractory complex perianal fistulas in patients with Crohn's disease. Methods: We did this randomised, double-blind, parallel-group, placebo-controlled study at 49 hospitals in seven European countries and Israel from July 6, 2012, to July 27, 2015. Adult patients (≥18 years) with Crohn's disease and treatment-refractory, draining complex perianal fistulas were randomly assigned (1:1) using a pre-established randomisation list to a single intralesional injection of 120 million Cx601 cells or 24 mL saline solution (placebo), with stratification according to concomitant baseline treatment. Treatment was administered by an unmasked surgeon, with a masked gastroenterologist and radiologist assessing the therapeutic effect. The primary endpoint was combined remission at week 24 (ie, clinical assessment of closure of all treated external openings that were draining at baseline, and absence of collections >2 cm of the treated perianal fistulas confirmed by masked central MRI). Efficacy was assessed in the intention-to-treat (ITT) and modified ITT populations; safety was assessed in the safety population. This study is registered withClinicalTrials.gov, numberNCT01541579 . Findings: 212 patients were randomly assigned: 107 to Cx601 and 105 to placebo. A significantly greater proportion of patients treated with Cx601 versus placebo achieved combined remission in the ITT (53 of 107 [50%] vs 36 of 105 [34%]; difference 15·2%, 97·5% CI 0·2–30·3; p=0·024) and modified ITT populations (53 of 103 [51%] vs 36 of 101 [36%]; 15·8%, 0·5–31·2; p=0·021). 18 (17%) of 103 patients in the Cx601 group versus 30 (29%) of 103 in the placebo group experienced treatment-related adverse events, the most common of which were anal abscess (six in the Cx601 group vs nine in the placebo group) and proctalgia (five vs nine). Interpretation: Cx601 is an effective and safe treatment for complex perianal fistulas in patients with Crohn's disease who did not respond to conventional or biological treatments, or both. Funding: TiGenix.